Herbal Medicine and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The potentially harmful effects of herbal remedies and herb-antiepileptic drug interactions in patients with epilepsy are reviewed by researchers at the Center for Integrative Complementary Medicine, and Division of Neurology and Toxicology, Shaare Zedek Medical Center, Jerusalem, Israel.